O uso de redes sociais como ferramenta de estímulo à participação na gestão do conhecimento dos processos organizacionais - Jucá, Paulyne (2011)
One of the present shortcomings in the application of knowledge management processes in organizations is the lack of a clear definition of how the knowledge management tool and activities are associated to the organizational process activities. This study evaluates the hypothesis that social networks can be used to encourage user participation in the knowledge management of organizational processes. The main contribution of this thesis is the methodology that was proposed in order to map the existing elements of knowledge on organizational processes in social networking functionalities. The application of this methodology allows a better understanding on how to perform knowledge management, combined with the daily activities of the organization. The case study with the teaching process has shown that user participation in the management of knowledge made through the social network is higher (and compatible with the best results in the existing social network) when users understand how to use the features of social network in their daily activities.